2022
DOI: 10.1155/2022/8552358
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Application Value of Remote ECG Monitoring in Early Diagnosis of PCI for Acute Myocardial Infarction

Abstract: The blockage of blood in the vessels results in heart attacks and cardiac arrests which are referred to as myocardial infarction. Early detection of such infarction is feasible through percutaneous coronary intervention (PCI) based on electrocardiogram (ECG) monitoring. The variations in blood flow and clot are precisely observed through periodic ECG monitoring and previous correlations. This article introduces a concentrated value assessment model (CVAM) for determining PCI levels in treating myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…We demonstrated the predictive power of the models, and the LDA model was superior to the other models, with an average AUC of 0. and prognosis of ACS. 13,14 However, only one ML algorithm was used to predict in-hospital mortality, 30-day CHF rehospitalization, and 180-day cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated the predictive power of the models, and the LDA model was superior to the other models, with an average AUC of 0. and prognosis of ACS. 13,14 However, only one ML algorithm was used to predict in-hospital mortality, 30-day CHF rehospitalization, and 180-day cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study verified the usefulness of ML techniques in predicting the diagnosis and prognosis of ACS. 13 , 14 However, only one ML algorithm was used to predict in‐hospital mortality, 30‐day CHF rehospitalization, and 180‐day cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%